Analisis Kesantunan Berbahasa Sebagai Dampak Dari Penerapan Pendidikan Karakter Pada Siswa - Afriana Afriana; Robby Satria Mandala (Prosiding, 2018)
This article is descriptive qualitative research. The object of this research is language politeness. Speech, including polite language is very important to be considered by the participants of communication (speakers and partners said) for the smooth communication. However, the reality nowadays, the Indonesian people have been getting a lot of influence from outside (modernization) so that the polite language is getting faded. Thus, the sublime character as an eastern man is increasingly invisible. Therefore, the researcher is interested in studying language politeness as the impact of character education which has two goals. First, describe the values of language politeness in communicating during the learning process in the classroom. Second, the impact of language politeness on character education. Participants in this study include students in grade IX SMPN 4 Batam Island. Data collection methods used observation, interview, and documentation. The results of this study 1. The values of language politeness in communicating during the learning process in the class of SMP Negeri 4 Batam that is Religious Value, Honest Value, Discipline, Tolerance, and Communication. The reason for choosing some of these character values is to remember less time to learn and limited participants’ ability. 2. the impact of language modesty on character education that is between the 18 values in character education there are some points that can be associated with language politeness include: appreciate achievement, friendly, caring environment, and social care. Language politeness can be integrated into sub-values in character education.